2015
DOI: 10.14763/2015.4.394
|View full text |Cite
|
Sign up to set email alerts
|

The net neutrality debate on Twitter

Abstract: The internet has been seen as a medium that empowers individual political actors in relation to established political elites and media gatekeepers. The present article discusses this "net empowerment hypothesis" and tests it empirically by analysing Twitter communication on the regulation of net neutrality. We extracted 503.839 tweets containing #NetNeutrality posted between January and March 2015 and analysed central developments and the network structure of the debate. The empirical results show that traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A temporal disaggregation might shed light on disagreements in earlier empirical research on the net neutrality debate. While one study found a limited equalisation of Twitter communication on the issue net neutrality (Schünemann et al, 2015), other research has argued for a decisive impact of online activists in this policy field (Faris et al, 2015). Yet both findings are not mutually exclusive.…”
Section: Policy Debates On Social Mediamentioning
confidence: 99%
“…A temporal disaggregation might shed light on disagreements in earlier empirical research on the net neutrality debate. While one study found a limited equalisation of Twitter communication on the issue net neutrality (Schünemann et al, 2015), other research has argued for a decisive impact of online activists in this policy field (Faris et al, 2015). Yet both findings are not mutually exclusive.…”
Section: Policy Debates On Social Mediamentioning
confidence: 99%
“…This involvement of online audiences in policy processes is not unique. An increasing number of case studies shows that online publics incidentally mobilize in relation to a range of policy agendas, be it internet regulations (Schünemann et al, 2015;Benkler et al, 2015), education policy (Supovitz et al, 2018;Schuster et al, 2021), climate change (Schünemann, 2020) or health policy (e.g. Bridge et al, 2021) among others.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they can refer to a particular post another user has made by retweeting it. As done in a lot of other Twitter studies, we take both actions as user interactions (Schünemann, Steiger, & Stier, 2015). In contrast, cross-referential cohesion is not based on user interactions but topical references.…”
Section: Expectations Of International Variationmentioning
confidence: 99%